Exercise-induced pu[l]monary hemorrhage: determination of mechanisms and potential treatments - Larson-Epp, Tammi Sue (Kansas State University, 2006)
Exercise-induced pulmonary hemorrhage (EIPH) or epistaxis has been recognized in racehorses since the 16th century. Since this time, great strides have been made in terms of identifying the lungs as the source of the hemorrhage via the endoscope, utilization of bronchoalveolar lavage to quantify the hemorrhage, and the discovery of successful treatments such as furosemide and the nasal strip that ameliorate, but do not abolish EIPH. It has been determined that, in addition to extremely high pulmonary arterial pressures and the negative intrapleural pressures being the major physiologic forces causing pulmonary capillary stress failure, other factors have the potential for influencing the severity of EIPH including locomotory impact trauma, inflammatory airway disease (IAD), upper airway obstruction, coagulation anomalies, and high blood viscosity. It has been hypothesized that EIPH is detrimental to performance and this was recently confirmed by Hinchcliff et al. in 2004. EIPH is a complex multi-factorial condition with much still unknown about the etiology, best method for diagnosis, and most effective form of treatment. Chapter one of this dissertation determined the effectiveness of a novel treatment, concentrated equine serum, in ameliorating EIPH via reduction of IAD. Chapter two refuted the hypothesis that herbal formulations commonly used in the field with anecdotal success would decrease EIPH by correcting coagulation deficits during exercise, as scientific efficacy was not evident, at least at the dose and duration used in our investigation. Chapter three addressed the dogma that EIPH only occurs during maximal intensity exercise, and in demonstrating significant EIPH during sub-maximal exercise, emphasized the role that the airways play in contributing to the initiation and severity of EIPH. Chapter four examined the occurrence and severity of EIPH in the horse’s canine counterpart, the racing Greyhound. The demonstrated presence of mild EIPH in the Greyhound, a physiologically similar yet different athlete in comparison to the horse sheds new light on the etiology of this condition in both species. The results of these investigations have advanced the frontiers of our knowledge concerning EIPH. Specifically, they have generated novel information on the mechanistic bases of EIPH and have provided evidence supporting additional treatment options for reducing the severity of EIPH in horses.
Keywords: horse; Greyhound; exercise-induced pulmonary hemorrhage; bronchoalveolar lavage; exercise; EIPH; Biology, Veterinary Science (0778)